The urban challenges in Lima. Mobility and public spaces against inequality - Kahatt, Sharif S. (2023)
Many of those large areas known as “part of the city” have not reached the minimum conditions to develop a sustainable ecosystem, that is, they lack a fundamental characteristic for the coexistence of their citizens: urbanity. Under these conditions, it is essential to identify the problems and turn them into opportunities for the transformation and improvement of the city as a space for citizen coexistence. Faced with this situation, urbanity is the key to achieving social equity, as well as mobility, and public space constitutes the elementary infrastructural tool to trace the path to egalitarian and inclusive development.